2015
DOI: 10.1213/ane.0000000000000585
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine Preferentially Inhibits the Function of Purinergic P2X7 Receptors Expressed in Xenopus Oocytes

Abstract: Lidocaine selectively inhibited the function of the P2X7 receptor expressed in Xenopus oocytes. This effect may be caused by acting on sites in the ion channel pore both extracellularly and intracellularly. These results help to understand the mechanisms underlying the analgesic effects of lidocaine when it is administered locally at least.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…As lidocaine has been shown to inhibit, in addition to VGSCs, other membrane-bound signaling molecules involved in oncogenesis 24 25 , the following experiments were employed to more conclusively demonstrate a link between VGSC activity and ERK1/2 phosphorylation and resultant invasive activity in SW620 colon cancer cells. Our previous work has demonstrated that Na V 1.5 VGSC isoform (encoded by SCN5A ) is responsible for invasivity of colon cancer cells as ‘knockdown’ of this isoform with either tetrodotoxin (TTX), a specific inhibitor of VGSCs, or siRNA-mediated targeting led to a significant loss of baseline invasion 4 .…”
Section: Resultsmentioning
confidence: 99%
“…As lidocaine has been shown to inhibit, in addition to VGSCs, other membrane-bound signaling molecules involved in oncogenesis 24 25 , the following experiments were employed to more conclusively demonstrate a link between VGSC activity and ERK1/2 phosphorylation and resultant invasive activity in SW620 colon cancer cells. Our previous work has demonstrated that Na V 1.5 VGSC isoform (encoded by SCN5A ) is responsible for invasivity of colon cancer cells as ‘knockdown’ of this isoform with either tetrodotoxin (TTX), a specific inhibitor of VGSCs, or siRNA-mediated targeting led to a significant loss of baseline invasion 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the protective effects observed in the it-Lido group might not limited to a pan-blockade of Na + channels. Recent reports also describe that lidocaine has a direct inhibitory effect on the purinergic P2X channels (37). Another important result of our study was that P2X channel antagonists iso-PPADS reduced VIBI in a similar way as lidocaine although not being associated with secondary effects of lidocaine such as neurotoxicity or lung edema formation (38).…”
Section: Discussionmentioning
confidence: 99%
“…The maximum concentration for inhibition is 282 ± 45 μmol/L. [ 30 ] These results are helpful for understanding the mechanism of the analgesic effect of systemically and locally administered lidocaine.…”
Section: Effect Of Lidocaine On Ligand-gated Channelsmentioning
confidence: 99%